STATIONARY AND NON-STATIONARY GROWTH OF INBOUND AND DOMESTIC TOURIST ARRIVALS IN INDIA: AN EMPIRICAL STUDY FROM 1990 TO 2018 - Dr. Debasish Batabyal, Dr. Shatrajit Goswami, Mr. Pratim Chatterjee, Dr. Abhijit Pandit, Mrs. Bani Ratna Padhi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Though continuous increase in tourist arrivals is the common form of presenting potentiality of tourism industry, there are many more issues involved in which stationary and non stationary states critically important for policy issue and future direction. This direction is also useful for contextualizing and comparing true and fair condition of tourism industry in a large country like India with 28 states and 8 UTs. The present article is a descriptive approach to analyse and exhibit stationary and non-stationary growth of domestic and international tourist arrivals in India in the light of the present context of COVID 19 outbreak for setting the future policy issues and recommendations.